1997
DOI: 10.1021/jp970945b
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Ionization of Methyl Chloride and Methyl Bromide by Collision with Metastable Neon Atoms

Abstract: Total and partial cross sections for Penning ionization of methyl chloride and methyl bromide by metastable neon atoms have been measured as a function of collision energy in the 0.040-0.15 eV range. The partial cross sections for the formation of CH 3 X + , CH 3 + , and CH 2 X + (X ) Cl, Br) show a decreasing trend, with different slopes, when the collision energy increases. The branching ratios indicate that the production of fragment ions is favored at higher energies. Based on new correlation rules that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…However, these investigations only indirectly confirm the basic idea on the above-mentioned Penning ionization mechanism. [2][3][4][5][6][7][8] Recently, we have performed direct observation of the steric effect in methyl chloride ionization by the metastable argon atom using the hexapole state-selector. 9 In the present study, we extend our exploration for obtaining experimental evidence for steric effect in Ar*( 3 P 2,0 ) ϩCHCl 3 →CHCl 2 ϩ ϩClϩArϩe Ϫ Penning ionization reaction using oriented CHCl 3 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…However, these investigations only indirectly confirm the basic idea on the above-mentioned Penning ionization mechanism. [2][3][4][5][6][7][8] Recently, we have performed direct observation of the steric effect in methyl chloride ionization by the metastable argon atom using the hexapole state-selector. 9 In the present study, we extend our exploration for obtaining experimental evidence for steric effect in Ar*( 3 P 2,0 ) ϩCHCl 3 →CHCl 2 ϩ ϩClϩArϩe Ϫ Penning ionization reaction using oriented CHCl 3 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Similar Penning ionization studies carried out at collision energies close to and above room temperature have shown that branching ratios do depend on E coll . In certain cases the ratio of dissociative PI increases with a growing collision energy, 8,10 and at other times it does the opposite. [4][5][6][7] We have not been able to conclusively es-…”
Section: Discussionmentioning
confidence: 97%
“…7 On the other hand, the fraction of electronically excited NH 3 + product ions decreases modestly with decreasing E coll , as found in the study of collisions between Ne( 3 P J ) atoms and NH 3 in the range of E coll 35 meV-200 meV (406 K-2320 K). 8 10 have investigated the Ne( 3 P J ) + CH 3 X (X=Cl and Br) reactions and reported an increasing fraction of parent ions with decreasing collision energy, whereas the fragment yield decreased with diminishing E coll . The general assumption in the interpretation of these experiments was that the propensities to form ions in the different electronic states is related to the orientation of the molecule relative to the angle of incidence of the metastable atom.…”
Section: Introductionmentioning
confidence: 99%
“…The red line is a sine waveform and the blue line is a cosine waveform. E(t) is the electric field of the light, a(t) is the Gaussian intensity envelope of the function, φ is the CEP as defined in Equation (3). (b) Shows the intensity I (t) of the sine and cosine laser pulses.…”
Section: Strong-field Few-cycle Laser Pulsesmentioning
confidence: 99%